Recent Publications (Quarterly Journal of Economics, 1954)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 68, Issue 2, May 1954, Pages 321–322, https://doi.org/10.1093/qje/68.2.321 Published: 01 May 1954